Entrepreneurial motivation and intention of undergraduates: investigating the moderating role of entrepreneurship course - Al-Jubari, Ibrahim; Hassan, Arif (Inderscience, 2015)
The purpose of the present study is to examine how basic psychological needs, as conceptualized in Self-Determination Theory, are related to attitudes, control beliefs and entrepreneurial intention of Theory of Planned Behaviour. Specifically, it aims at understanding the relationship between autonomy and competence and students’ intention to start their own businesses. It further aims at testing the direct and indirect effects on entrepreneurial intention. In addition, entrepreneurship education and training could be one of the factors that help in fostering positive attitudes about entrepreneurship and in unleashing entrepreneurial skills and developing the required competencies. Thus, the present study also aims at examining the moderation role entrepreneurship course on students’ inclination to be entrepreneurs.